2012
DOI: 10.1209/0295-5075/97/47004
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of radiation of optically active molecules with chiral nano-meta-particles

Abstract: The radiation of optically active (chiral) molecule placed near chiral nanosphere is investigated. The optimal conditions for engineering of radiation of optically active (chiral) molecules with the help of chiral nanoparticles are derived. It is shown that for this purpose, the substance of the chiral particle must have both ε and µ negative (double negative material (DNG)) or negative µ and positive ε (µ negative material (MNG)). Our results pave the way to an effective engineering of radiation of "left" and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 21 publications
4
35
0
1
Order By: Relevance
“…Following the semiclassical theory of spontaneous emission [19][20][21], we approximate this chiral source to be…”
Section: Directional Quantum Emitter Couplingmentioning
confidence: 99%
“…Following the semiclassical theory of spontaneous emission [19][20][21], we approximate this chiral source to be…”
Section: Directional Quantum Emitter Couplingmentioning
confidence: 99%
“…For example, it was a powerful method to differentiate a secondary structure of proteins which can appear in the forms of α-helix, random coil, or β-sheet. Recently the concepts of chirality and CD have been brought to the field of plasmonics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . One of the motivations for this development is plasmon-enhanced sensing of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that enantiomers exhibit enantio-specific coupling to the modes of a chiral scatterer, and that chiral structures can substantially modify the decay rate and radiation pattern of chiral molecules [27]. Here, we consider the radiation of a chiral molecule in the vicinity of our PT-symmetric structure, which, importantly, contains no chiral constituents.…”
Section: Chiral Emittersmentioning
confidence: 99%
“…The electric and magnetic dipoles are located 20 nm away from the interface, in the xy-plane with an angle θ between them. We assume that the ratio between the magnetic and electric dipoles is ξ = 0.1c, where c is the speed of light [27,34]. From Fig.…”
Section: Chiral Emittersmentioning
confidence: 99%